First Molecular Detection of Infectious Spleen and Kidney Necrosis Virus ( ISKNV ) and the Parasite Centrocestus formosanus in the Ornamental Fish Platy ( Xiphophorus maculatus ) in Chile - Jaiber J. Solano‐Iguaran; Felipe Pontigo; Dennis Cisterna; Carla Anguita; Margarita P. González‐Gómez (Journal of Fish Diseases, 2026)
Infectious Spleen and Kidney Necrosis Virus (ISKNV) is a significant fish pathogen historically reported in East and Southeast Asia and increasingly detected in other regions, often in association with the international movement of ornamental fish. Centrocestus formosanus is a digenean trematode of sanitary and economic relevance, with zoonotic potential, that uses snails and fish as intermediate hosts. In this study, ornamental fish representing 24 species were sampled from 13 quarantine facilities across Chile. ISKNV was detected in samples of platy fish ( Xiphophorus maculatus ) from two quarantine facilities in the Metropolitana district in Chile, both supplied by the same exporter in the State of Florida (United States). C. formosanus metacercariae were also detected in the gills of two ISKNV‐positive platy fish. These results represent the first molecular detection of ISKNV and C. formosanus in ornamental fish in Chile and highlight the relevance of targeted surveillance for high‐risk pathogens in imported ornamental fish.

Carbon nanotube-based solid-state mid-infrared electrochromic devices for smart outdoor thermal management - Ke Jiao; Zongtao Zhang; Yifei Liu; Jin Li; Chao Xue; Jing Zhang; Yunxiang Chen; Zhang Chen; Xinghui Hou; Liying Zhang; José V. Anguita; Wei Zhang; et al. (Chemical Engineering Journal, 2025)

Flexible and large-area electrochromic infrared devices with superior modulation functionality - Zongtao Zhang; Yifei Liu; Ke Jiao; Yunxiang Chen; Jing Tong; Jin Li; Miaoran Xu; Chao Xue; José V. Anguita; Jing Zhang; Kai Yang; Wei Zhang; et al. (Chemical Engineering Journal, 2025)

Embedded software of the KM3NeT central logic board - S. Aiello; A. Albert; S. Alves Garre; Z. Aly; A. Ambrosone; F. Ameli; M. Andre; E. Androutsou; M. Anghinolfi; M. Anguita; L. Aphecetche; M. Ardid; et al. (Computer Physics Communications, 2024)

Biofuel Impact on Diesel Engine After-Treatment: Deactivation Mechanisms and Soot Reactivity - E. Iojoiu; V. Lauga; J. Abboud; G. Legros; J. Bonnety; P. Da Costa; J. Schobing; A. Brillard; G. Leyssens; V. Tschamber; P. Anguita; J. G. Vargas; et al. (Emission Control Science and Technology, 2018)

Economic assessment of fidaxomicin for the treatment of Clostridium difficile infection (CDI) in special populations (patients with cancer, concomitant antibiotic treatment or renal impairment) in Spain - C. Rubio-Terrés; J. Cobo Reinoso; S. Grau Cerrato; J. Mensa Pueyo; M. Salavert Lletí; A. Toledo; P. Anguita; D. Rubio-Rodríguez; M. Watt; R. Gani (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

Spatial Modeling of Tropical Deforestation Using Socioeconomic and Biophysical Data - S. Rivera; P. Martinez de Anguita; R. D. Ramsey; T. A. Crowl (Small-scale Forestry, 2013)